Supergirl. The complete first season [videorecording (DVD)] - Berlanti, Greg (Supergirl (TV series), 2016)
Born on the doomed planet Krypton, Kara Zor-El escaped at the same time as her cousin, Superman, but didn't arrive on Earth until years later after being lost. Raised by her adopted family, the Danvers, Kara grew up in the shadow of her foster sister, Alex, and learned to hide the phenomenal powers she shares with her famous cousin. Kara has spent so many years trying to fit in that she forgot to ever stand out.